Small Tropical Mammals Can Take the Heat: High Upper Limits of Thermoneutrality in a Bornean Treeshrew - Thonis, Anna; Ceballos, Ruben Michael; Tuen, Andrew Alek; Lovegrove, Barry G.; Levesque, Danielle L. (Physiological and biochemical zoology, 2020)
Tropical ectotherms are generally believed to be more vulnerable to global heating than temperate species. Currently, however, we have insufficient knowledge of the thermoregulatory physiology of equatorial tropical mammals, particularly of small diurnal mammals, to enable similar predictions. In this study, we measured the resting metabolic rates (via oxygen consumption) of wild-caught lesser treeshrews (Tupaia minor, order Scandentia) over a range of ambient temperatures. We predicted that, similar to other treeshrews, T. minor would exhibit more flexibility in body temperature regulation and a wider thermoneutral zone compared with other small mammals because these thermoregulatory traits provide both energy and water savings at high ambient temperatures. Basal metabolic rate was on average 1.03±0.10 mL O2 h−1 g−1, which is within the range predicted for a 65-g mammal. We calculated the lower critical temperature of the thermoneutral zone at 31.0°C (95% confidence interval: 29.3°–32.7°C), but using metabolic rates alone, we could not determine the upper critical temperature at ambient temperatures as high as 36°C. The thermoregulatory characteristics of lesser treeshrews provide a means of saving energy and water at temperatures well in excess of their current environmental temperatures. Our research highlights the knowledge gaps in our understanding of the energetics of mammals living in high-temperature environments, specifically in the equatorial tropics, and questions the purported lack of variance in the upper critical temperatures of the thermoneutral zone in mammals, emphasizing the importance of further research in the tropics.